1999
DOI: 10.1055/s-1999-3490
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to the Synthesis of Psilocybin and a Facile Method for Preparing the O-Acetyl Prodrug of Psilocin

Abstract: An improved procedure to accomplish the O-phosphorylation of 4-hydroxy-N,N-dimethyltryptamine (psilocin 5) is reported that utilizes reaction between the O-lithium salt of 5 and tetra-Obenzylpyrophosphate. The O-benzyl groups were removed by catalytic hydrogenation over palladium on carbon to afford N,N-dimethyl-4-phosphoryloxytryptamine (psilocybin, 1). In view of difficulties encountered in the preparation of 1, it is suggested that 4-acetoxy-N,N-dimethyltryptamine (2) may be a useful alternative for pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 7 publications
3
77
0
Order By: Relevance
“…The compounds were originally synthesized by chemists at the Sandoz laboratories in Switzerland (Hofmann et al, 1958;Troxler et al, 1959). Several investigators have subsequently reported on the chemical synthesis of psilocybin (Ono et al, 1973;Repke et al, 1981;Ametamey et al, 1998;Yamada et al, 1998;Nichols and Frescas, 1999;Sakagami and Ogasawara, 1999;Yamada, 2000;, but only a few on the synthesis of psilocin (Nichols and Frescas, 1999;.…”
Section: Chemical Synthesis Of Psilocybin and Psilocinmentioning
confidence: 99%
“…The compounds were originally synthesized by chemists at the Sandoz laboratories in Switzerland (Hofmann et al, 1958;Troxler et al, 1959). Several investigators have subsequently reported on the chemical synthesis of psilocybin (Ono et al, 1973;Repke et al, 1981;Ametamey et al, 1998;Yamada et al, 1998;Nichols and Frescas, 1999;Sakagami and Ogasawara, 1999;Yamada, 2000;, but only a few on the synthesis of psilocin (Nichols and Frescas, 1999;.…”
Section: Chemical Synthesis Of Psilocybin and Psilocinmentioning
confidence: 99%
“…Known N-methylated derivatives 3 and 4 were synthesized following published procedures. 5,9,10 Treatment of 4-benzyloxyindole with oxalyl chloride and then with dimethylamine gave the 3-substituted oxamide. Amide reduction (LAH), N-methylation (NaH, MeI), and hydrogenation (H 2 , Pd(OH) 2 ) afforded N-methylpsilocin, 3.…”
mentioning
confidence: 99%
“…The compounds prepared (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) 8 are shown in Figure 2. Known N-methylated derivatives 3 and 4 were synthesized following published procedures.…”
mentioning
confidence: 99%
“…The solution of 4-benzyloxy-N,N-dimethyltryptamine [15,16] substance 1 (2.6 mg, 0.009 mmol) in dry DMF (300 µl) was added and the mixture stirred for further 20 min at 0°C. Subsequently a solution of [ 3 H]methyl iodide (85 mCi, 1.176×10 −3 mmol, American Radiolabelled Chemicals, St. Louis, USA) in toluene (150 µl) was added and the resulting mixture was stirred overnight.…”
Section: Synthesis Of Tracersmentioning
confidence: 99%